2002
DOI: 10.1073/pnas.202392199
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of new cyclooxygenase inhibitors on gastric ulcer healing: Shifting the angiogenic balance

Abstract: Delayed gastric ulcer healing is a well recognized problem associated with the use of cyclooxygenase (COX) inhibitors. In contrast, NO-releasing COX inhibitors do not interfere with ulcer healing. These divergent effects may in part be due to differences in their effects on platelets, which are known to influence ulcer healing. Therefore, we compared the effects of a nonselective COX inhibitor (flurbiprofen), a nitric oxide-releasing COX inhibitor (HCT-1026), and a selective COX-2 inhibitor (celecoxib) on gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 39 publications
10
105
0
2
Order By: Relevance
“…23,24 This is particularly so at the margin of gastric ulcers (both in humans and in rodent models), 25,26 and contributes significantly to healing. 27,28 In the present study, we observed that male Muc-2-deficient mice had significantly reduced up-regulation of COX-2, compared with female . Expression of Muc-2 and Muc-5ac in mice with gastric ulcers induced by serosal application of acetic acid (10 days before harvesting of tissue).…”
Section: Up-regulation Of Cox-2 Expression Is Impaired In Male Muc-2-supporting
confidence: 58%
“…23,24 This is particularly so at the margin of gastric ulcers (both in humans and in rodent models), 25,26 and contributes significantly to healing. 27,28 In the present study, we observed that male Muc-2-deficient mice had significantly reduced up-regulation of COX-2, compared with female . Expression of Muc-2 and Muc-5ac in mice with gastric ulcers induced by serosal application of acetic acid (10 days before harvesting of tissue).…”
Section: Up-regulation Of Cox-2 Expression Is Impaired In Male Muc-2-supporting
confidence: 58%
“…Importantly, consistent with the known ability of COX-2 inhibitors to interfere with neoangiogenesis (4,41), in our series, celecoxib treatment was associated with the shifting of the balance between circulating levels of VEGF and endostatin toward an ''antiangiogenetic'' state, as also reported in a preclinical model of gastric ulcer healing (42). In conclusion, we reported the first evidence in humans that celecoxib, besides the direct effects on tumor proliferative potential and neoangiogenesis, restores~expression by TIL in primary cervical tumors, suggesting that a positive modulation of immune function may serve as an additional mechanism supporting the antitumor effect of this class of drugs.…”
Section: Discussionsupporting
confidence: 90%
“…10,11,13,14 Its role is mediated by a number of molecules such as VEGF-A, CD44 and matrix metalloproteinases, 15 and results in the induction of tumor angiogenesis, increased invasiveness, apoptosis and immune surveillance inhibition and increased cell proliferation. Also, increased COX-2 expression was associated with poor prognosis in a number of malignancies, [16][17][18] and head and neck squamous cell carcinoma, although the small number of patients enrolled in the studies for head and neck squamous cell carcinoma does not permit the extraction of valid conclusions. 10,11,13,14 VEGF-C is a member of the VEGF family and along with VEGF-D is considered to be responsible for tumor lymphangiogenesis and lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%